Implementation of Education Rights Fulfillment for Street Children by the Local Government - Aurora Virgonia; Rozidateno Putri Hanida; Roni Eka Putra (Jurnal Administrasi dan Kebijakan Publik, 2020)
Children and education are two related elements to each other. Both the central and local governments have also issued policies that govern the education of children. But in fact, education for the street children has been still faced with some obstacles during the implementation. This research was conducted in Padang Municipality. This research was the result of the field studies to describe and analyze how was the effort of the fulfillment of the education rights of the street children in Padang Municipality. The research was conducted using qualitative research method where data collection techniques by interviews with several related stakeholders to this policy, observed the phenomena that have related to the policy, and do library research from any references such as the government's document and scientific research and tested with by triangulation sources techniques. The research result shows that there are some difficulties during the fulfillment of street children's education to implement by the few stakeholders. In addition, the incapability of these polices to provided clarity to each process of the policy implementation so that the output of the policy has not been able to be reached to the maximum